The mechanism of hydration reaction of granulated blast furnace slag-steel slag-refining slag-desulfurization gypsum-based clinker-free cementitious materials. (December 2021) - Liu, Zhengyu; Ni, Wen; Li, Ying; Ba, Haojing; Li, Ning; Ju, Yongjian; Zhao, Ben; Jia, Guoliang; Hu, Wentao
Abstract: In this study, refining slag containing high hydration active component C12 A7 was added in GBFS−SS−DG−based clinker−free cementitious material. The optimum was determined by an orthogonal test and the influence of heat treatment was studied. The participation of refined slag makes the compressive strength of 3 days reached 27.4 MPa, 60.6% of that at 56 days, which overcomes the shortcoming of low initial strength of GBFS−SS−DG−based clinker−free cementitious material. Microscopic analysis showed that quantities of ettringite occurred in 3 days. During the hydration, C3 AH6 was formed by the hydration reaction of C3 A and C12 A7 and then reacted with the C S ‾ H2 to form ettringite which constituted the basic framework. Under the alkaline condition provided by steel slag, SiO4 tetrahedra and AlO4 tetrahedra were constantly dissociated from GBFS, then C–S–H gels and ettringite were further developed, which was corroborated by results of IR and XPS. In middle and late period, amounts of C–S–H gels wrapped AFt crystals and filled the pores, and finally formed a unified composite structure, which was responsible for the high strength of 43.0 MPa at 28 days. Highlights: The synergy of GBFS, SS, RS and DG enabled compressive strength to reach 27.4, 35.7, 43.0 and 45.3 MPa at 3, 7, 28, and 56 days. 15% refining slag makes the system contain a lot of C12 A7 which contributes most to initial strength. Crystal transformation of AFt was indicated by XPS analysis of S 2p and Al 2p. The application of this green materials helps to reduce the solid waste pushing stock and carbon dioxide emissions.